PENGARUH LAMA PENGUAPAN PELARUT (DIKLOROMETANA) DAN KONSENTRASI UMPAN TERHADAP FILTRASI SARIBUAH APEL PADA MEMBRAN SELULOSA ASETAT MIKROBIAL - Abdul Aziz Darwis, Proyoga Suryadarma dan Ely Rosita (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTPorous membrane in membrane technology is achieved by controlling solvent evaporation time to obtain various pore size.  This various size is expected to affect filtration with various feed concentration at which a part of soluble particles could be retained.  Solvent evaporation time and feed concentration effect on flux and turbidity of apple juice filtration is studied.